A Correlation Between Pericarpium Citri Reticulatae Volatile Components and the Change of the Coexisting Microbial Population Structure Caused by Environmental Factors During Aging - Yang, Fangqing; He, Liying; Shen, Mengyuan; Wang, Fu; Chen, Hongping; Liu, Youping (Frontiers in Microbiology, 2022)
Pericarpium Citri Reticulatae (PCR) is a natural citrus by-product with beneficial health and nutritive properties that is used widely in food and is an ingredient in traditional Chinese medicine. PCR improves gradually with aging. However, the present research has not yet revealed the reasons for this. Some data prove the important role of microorganisms in the quality of tobacco and fermented tea with the time of the aging of these foods. Our studies further proved that the coexisting Aspergillus niger plays an important role in the change of flavonoids and volatile oil in PCR during this process. Therefore, we put forward that longer storage is better for PCR and is highly correlated with the change of the coexisting microbial population structure caused by environmental factors. Samples of PCR aged in Beijing, Sichuan, Guangdong, and Yunnan were collected at different time points. Using GC/MS and high throughput 16S rDNA and ITS sequencing techniques, massive changes in volatile profile and microbial communities were observed during aging. Spearman correlation analysis indicated that Exobasidium, Xeromyces, Pseudocercospora, Russula, Aspergillus, Herbaspirillum, Sphingomonas, and Streptococcus, which are the dominant microbial genera in Sichuan and Guangdong showed strong connections with volatile components of chemical markers. It was preliminarily verified that the changes of volatile components for PCR are highly correlated with the change of the coexisting microbial population structure caused by environmental factors, providing a new idea for the research on the aging mechanism of PCR and key influencing factors of aging quality.